Floor Exercise Digital Book Using the Circuit Elephant Game to Improve the Accuracy of Forward Roll Movements in Elementary School Students - Mujiono; Andrinugroho, Aryo; Buchori, Achmad (Jurnal Pendidikan Indonesia, 2025)
Field observations show that many elementary school students still have difficulty performing forward rolls correctly. This study aims to develop digital learning media as an interactive book combining elements of the game "Elephant Circuit". The method used is Research and Development (R&D) with the ADDIE approach. The study subjects were all 20 fourth-grade students, using a saturated sampling technique. The study used a one-group pretest-posttest design. Data collection methods used include questionnaires, interviews, tests, and documentation. The instruments used include questionnaires and test questions. Data analysis techniques used N-Gain, t-test and MANOVA. The study's results, namely the validation results, indicate that the media is classified as very feasible. The t-test results show a significance value (Sig. 2-tailed) < 0.001, so there is a significant difference between student learning outcomes before and after being given treatment in the form of using digital book media. Based on the results of the regression analysis, it is known that student activity has a positive but insignificant effect on forward roll skills. It is concluded that student activity does not contribute significantly to improving forward roll skills. Based on the regression analysis results, it can be concluded that student activity has a positive but insignificant effect on the forward roll skill in Physical Education (PJOK). This research implies that this digital book is an effective and innovative alternative learning medium, particularly in supporting elementary school student's mastery of basic floor gymnastics movements.